Analysis Of Risk Factors For Diabetic Retinopathy: Literature Review - Mardika I. S. P. Laode; Ruslinah HTM; Rachmat Latief (Jurnal EduHealth, 2024)
Diabetes mellitus (DM) is a global epidemic and affects populations in both developing and developed countries, with varying levels of health care and resources. different. DM is a chronic disease and generally degenerative in nature which if not treated properly will cause various complications. Diabetic Retinopathy (DR) is the main complication of Diabetes Mellitus (DM) which is the main cause of blindness. Objective: This literature aims to analyze the risk factors for the occurrence of retinopathy. diabetic. Method: This research uses literature method review , a scientific article or journal downloaded from PubMed , Garuda Portal, and Google Scholar with SINTA IV and V standards in the time span 20 20 -202 4.  The keywords in this article search are Diabetic Retinopathy and risk factors. Results: In this literature, it was found namely 20 research articles that report risk factors for the occurrence of retinopathy diabetic. Conclusion: There are several risk factors for retinopathy. Diabetic, namely high cholesterol levels, high blood pressure, being pregnant, smoking habits, and blood sugar levels that are not well controlled.